Distinct Roles of m5C RNA Methyltransferase NSUN2 in Major Gynecologic Cancers - Wang, Lingfang; Zhang, Jian; Su, Yingfeng; Maimaitiyiming, Yasen; Yang, Siqi; Shen, Zhangjin; Lin, Shitong; Shen, Shizhen; Zhan, Guankai; Wang, Fenfen; Hsu, Chih-Hung; Cheng, Xiaodong (Frontiers in Oncology, 2022)
RNA methylation has recently emerged as an important category of epigenetic modifications, which plays diverse physiopathological roles in various cancers. Recent studies have confirmed the presence of 5-methylcytosine (m5C) modification on mammalian mRNAs, mainly modified by NSUN2, but little is known about the underlying functions of m5C. Gynecologic cancers are ma-lignancies starting from women’s reproductive organs. The prevalence of gynecologic cancers leads to giant economic burden and public health concern. In this study, we investigated the potential biological functions of NSUN2 in common gynecologic cancers including cervical cancer, ovarian cancer and endometrial cancer. Remarkably, distinct scenarios were found. The levels of NSUN2 did not show alteration in endometrial cancer, and in ovarian cancer depletion of up-regulated NSUN2 did not reduce carcinogenesis in cancer cells, suggesting the upregulated NSUN2 might be an incidental effect. On the contrary, NSUN2 played a role in tumorigenesis of cervical cancer; depletion of upregulated NSUN2 notably inhibited migration and invasion of cancer cells, and only wild-type but not catalytically inactive NSUN2 rescued these malignant phenotypes of cancer cells. Mechanistically, NSUN2 promoted migration and invasion by leading to m5C methylation on KRT13 transcripts, and methylated KRT13 transcripts would be recognized and stabilized by an m5C reader, YBX1. Collectively, these results not only displayed the nature of diversity among human malignancies, but also demonstrated a novel NSUN2-dependent m5C-YBX1-KRT13 oncogenic regulatory pathway.